Development and validation of a quality of life and treatment satisfaction measure in canine osteoarthritis - Gildea, Edwina; Scales-Theobald, Emma; Thompson, Jill; Cook, Alasdair; Forde, Katie; Skingley, George; Lawrie, Sophie; Williamson, Nicola; Panter, Charlotte (Frontiers in Veterinary Science, 2024)
Canine osteoarthritis (OA) causes pain and mobility impairment. This can reduce dog quality of life (QoL), owner QoL and owners' satisfaction with, and adherence to, treatments. No existing canine OA-specific instrument exists that assesses all three impacts. This study aimed to develop and psychometrically evaluate an owner-completed canine OA-specific measure of dog QoL, owner QoL and owner treatment satisfaction (TS); the "Canine OA Quality of Life and Treatment Satisfaction Questionnaire" (CaOA-QoL-TS). The CaOA-QoL-TS was developed using a conceptual model derived from a meta-synthesis of published literature followed by cognitive interviews with ten owners of dogs with OA, to evaluate content validity. Based on interview findings, ten items were reworded, four removed, and two added; resulting in 26 items that all owners understood and considered relevant. Recall period and response options were well understood and appropriate to almost all owners. To evaluate its psychometric properties, the CaOA-QoL-TS (draft 26-item version) was administered, across six timepoints in a phase 4 field study, to owners of OA treated dogs, recruited from veterinary practices (N=93). Inter-item correlations suggested items clustered into three distinct domains: Dog QoL, Owner QoL and TS, as hypothesized. Confirmatory factor analysis supported deletion of two items and calculation of the three domain scores, with acceptable model fit. The resulting 24-item CaOA-QoL-TS instrument demonstrated strong internal consistency and good to excellent test-retest reliability. Convergent validity was supported by moderate to strong correlations with concurrent measures. Known groups validity was supported by statistically significant differences between groups categorized by owner global impression of QoL. Ability to detect change was demonstrated through statistically significant improvements over time in Owner and Dog QoL, with larger within-group effect sizes reported for the mean of 'improved' dogs compared to the mean of 'stable' dogs. Only a small sample of dogs worsened throughout the study. Anchor-based analyses supported -0.9 and -1.0-point within-group responder definitions for dog and owner QoL domains, respectively. Findings support the content validity of the CaOA-QoL-TS in canine OA. The 24-item CaOA-QoL-TS is a reliable and valid instrument to measure owner and canine QoL and TS and is sensitive to improvements following OA treatment.